Analisis Potensi Daya Tarik Dan Motivasi Berkunjung Wisatawan Di Makam Bung Karno - Harahap, Wandy Wahyu; Febryanti, Dea Pascha; Simanungkalit, Dion Berkah Marihot; Hamid, Faizah Rahmah; Rahman , Fazlul; Sa'diyah, Ilmatus; Alawi, A. Muammar (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
Various ethnicities, cultures, religions, tribes, races come to visit Bung Karno's grave to make a pilgrimage in their own way. This is proof that the Indonesian nation is a nation rich in diversity. Although diverse, all of them are united by a nationalist spirit, with a high spirit of nationalism, all diversity can be united. Analysis of the attractiveness and motivation of visitors in general is needed to find out how much the spirit of nationalism of the Indonesian people in appreciating and continuing the services of its heroes, especially Bung Karno as the first President of the Republic of Indonesia. The method used is the literature study method and interviews. Data was obtained based on interviews with the caretaker of the place and with the results of his own observations. From the results it was found that Bung Karno's charismatic figure is still the main reason visitors come as a form of appreciation to him. His struggle certainly cannot only be felt before independence, but for his struggle since then, the enjoyment of independence can still be felt.